Emerging of Fatal Colitis with Multidrug-Resistant Candida glabrata after Small Bowel Transplantation. (10th September 2021) - Zareshahrabadi, Zahra; Shafiekhani, Mojtaba; Nikoupour, Hamed; Nouraei, Hasti; Morovati, Hamid; Zomorodian, Kamiar
Abstract : Background . Small bowel transplantation is a potential option for patients with intestinal-failure, and the incidences of infections caused by Candida species that are more resistant to antifungal drugs are increasing in these patients. In this manuscript, we reported a case of fatal colitis after small bowel transplantation induces by multidrug-resistant (MDR) Candida glabrata. Case Presentation . A 52-year-old man has undergone an extensive small bowel resection with the length of the remaining bowel which was less than 40 cm who became a candidate for transplantation. Four months after transplantation, the patient experienced severe bloody diarrhea with abdominal distension. Ileoscopy and colonoscopy did not show neither pathological change and rejection nor cytomegalovirus (CMV) infection posttransplantation. Abdomen computed tomography showed diffuse moderate small bowel wall thickening. After detection of budding yeast in the stool samples, stool culture was positive for Candida, DNA was extracted, and ITS1-5.8s-ITS2 region of the fungal agent was amplified. Sequencing analysis of PCR and antifungal susceptibility testing revealed that this isolate was multidrug-resistant C. glabrata . Besides, there was no evidence for other pathogens known to cause infection in various laboratory tests. Immediate antifungal treatments with caspofungin remained unsuccessful, and on the eighteenth day of admission, the patient expires with septic shock. Conclusion . These findings highlight the challenging management of candidiasis in patients with small bowel transplantation. Infectious diseases due to MDR organisms have emerged as a vital clinical problem in this patient population.